2019
DOI: 10.12659/msm.917401
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitivity of Reality Monitoring to Fluency: Evidence from Behavioral Performance and Event-Related Potential (ERP) Old/New Effects

Abstract: Background: Item memory and source memory are differently processed with both behavioral and event-related potential (ERP) evidence. Reality monitoring, a specific type of source memory, which refers to the ability to differentiate external sources from internal sources, has been drawing much attention. Among factors that have an impact on reality monitoring, fluency has not been well-studied. Therefore, the current study aimed to investigate whether fluency could affect reality monitoring, through observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The results depicted that there were processing differences in the mechanisms, rather than just differences in memory strength, between item and source memory, specifically a subtype of source memory. These findings provide additional evidence for dual-process models of memory (Cooper et al 2017;Leynes et al 2017;Nie et al 2019b;Ye et al 2019), rather than models that claim a single process during the test (Hayes et al 2017;Slotnick and Dodson 2005).…”
Section: Source Memory Of Colors: No Expectation Leads To Better Retr...mentioning
confidence: 71%
See 2 more Smart Citations
“…The results depicted that there were processing differences in the mechanisms, rather than just differences in memory strength, between item and source memory, specifically a subtype of source memory. These findings provide additional evidence for dual-process models of memory (Cooper et al 2017;Leynes et al 2017;Nie et al 2019b;Ye et al 2019), rather than models that claim a single process during the test (Hayes et al 2017;Slotnick and Dodson 2005).…”
Section: Source Memory Of Colors: No Expectation Leads To Better Retr...mentioning
confidence: 71%
“…Two subtypes of episodic memory, namely item memory and source memory, have been identified as dissociable. Item memory allows us to distinguish previously experienced items from novel items, while source memory enables us to retrieve the peripheral details and the contexts from which an event was originally acquired (Ehrenberg and Klauer 2005;Li and Nie 2021;Nie et al 2019a;Nie et al 2019b;Ye et al 2019).…”
Section: The Pre-existing Expectation On Episodic Memory: Mixed Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, analysis of RTs during encoding revealed that over‐estimators responded faster than under‐estimators did during encoding, which is consistent with a large body of prior findings on fluency (Alter & Oppenheimer, 2009; Bader & Mecklinger, 2017; Bruett & Leynes, 2015; Castel, McCabe, & Roediger, 2007; Cermak, Verfaellie, Sweeney, & Jacoby, 1992; Doss, Bluestone, & Gallo, 2016; Hertzog, Dunlosky, Robinson, & Kidder, 2003; Kurilla & Westerman, 2008; Leynes & Addante, 2016; Leynes & Zish, 2012; Li, Gao, Wang, & Guo, 2015; Nie, Xiao, Liu, Zhu, & Zhang, 2019; Serra & Dunlosky, 2005; Thapar & Westerman, 2009; Volz, Schooler, & von Cramon, 2010; Westerman, 2008; Whittlesea & Leboe, 2000, 2003). Thus, subjects could have responded more quickly to items by virtue of the items seeming more fluent.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological analyses followed our previous studies and examples of others' works (Nie et al, 2014(Nie et al, , 2016(Nie et al, , 2019Nie & Yu, 2021;Picton et al, 2000;Ye et al, 2019;Zhou et al, 2020). We followed our own prior research as well as others because we averaged the waveforms as others had, but our previous studies had focused upon memory rather than the current that focused on inductive reasoning task.…”
Section: Data Analysesmentioning
confidence: 99%